ANALISIS PENGGUNAAN BAHASA INDONESIA FORMAL DAN INFORMAL TERHADAP KOMUNIKASI ANTAR MAHASISWA/I DI KAMPUS UNIVERSITAS NEGERI MEDAN - Amalia Tri Wardani; Hotma Uli Christianita; Sofia Ananta Aruan; Yesohaya Divina Kaban (Ekasakti Jurnal Penelitian dan Pengabdian, 2024)
Formal language is the type of language used in formal situations such as academic activities on campus. This language does not include colloquial language or non-formal words. Meanwhile, non-formal language is a type of speech used in informal or non-formal situations, such as conversations between friends or family members. Speaking informally becomes more refined; it may include colloquialisms, non-standard expressions, and more. This research aims to analyze the use of formal and informal Indonesian in student communication at Medan State University. The data collection method used is the use of a participatory observation form via a questionnaire which is often called Google Form, to collect information about several students. Students are then given a form and fill in the answers to questions which will later become data for researchers. The results of the research that has been carried out show that as many as 32.3 percent or 10 out of 31 respondents, according to the analysis findings, rarely use formal language. Then, 3.2% or 1 out of 31 respondents stated that they had never spoken official Indonesian. Furthermore, as many as 35.5 percent or 11 out of 31 respondents consistently spoke formal Indonesian. Finally, 9 out of 31 respondents, or 29% of the sample, said that they often spoke Indonesian formally. Based on the proportion seen, as many as 80.6 percent, or 25 out of 31 respondents, support the use of formal Indonesian in academic settings on campus. Finally, around 12.9% of respondents, or 4 out of 31 respondents, felt it was permissible to use formal Indonesian in an academic setting in class. In addition, final data showed that around 6.5 percent, or 2 out of 31 respondents, did not find the use of formal Indonesian in the classroom unpleasant. The Medan State University campus can benefit from the implications of this research by developing effective communication strategies.